Widespread siRNA “off-target” transcript silencing mediated by seed region sequence complementarity - Jackson, Aimee L. (Cold Spring Harbor Laboratory Press, 2006)
Transfected siRNAs and miRNAs regulate numerous transcripts that have only limited complementarity to the active strand of the RNA duplex. This process reflects natural target regulation by miRNAs, but is an unintended (“off-target”) consequence of siRNA-mediated silencing. Here we demonstrate that this unintended off-target silencing is widespread, and occurs in a manner reminiscent of target silencing by miRNAs. A high proportion of unintended transcripts silenced by siRNAs showed 3' UTR sequence complementarity to the seed region of the siRNA. Base mismatches within the siRNA seed region reduced the set of original off-target transcripts but generated new sets of silenced transcripts with sequence complementarity to the mismatched seed sequence. An inducible shRNA silenced a subset of transcripts that were silenced by an siRNA of the same sequence, demonstrating that unintended silencing is sequence mediated and is independent of delivery method. In all cases, off-target transcript silencing was accompanied by loss of the corresponding protein and occurred with dependence on siRNA concentration similar to that of silencing of the target transcript. Thus, short stretches of sequence complementarity to the siRNA or shRNA seed region are key to the silencing of unintended transcripts.